Postcolonial children's literature: songs of innocence and experience with reference Tomarina Budhos' Ask me no questions (2007), and Cathryn Clinton's A stone in my hand (2002) - Elshaikh, Ebtihal Abdelsalam (online, 2016)
Abstract: The purpose of this paper is to show how psychological trauma resulted from conflicts such as colonialism, immigration, racism, wars and invasion; and even gender discrimination makes its way into postcolonial children's literature. For example, some contemporary writers of children's literature depict the painful experience of young immigrants who are living under constant stress and tension. Others try to depict how the Middle East conflicts and turmoil affect children living under occupation. In all of these cases, children are highly at risk of psychological trauma. This paper is going to discuss two contemporary children's novels which address the issues of immigration and war conflicts: Marina Budhos' Ask Me no questions (2007), and Cathryn Clinton's A Stone in my Hand (2002). They were chosen to reflect not only the variety of children's literature available, but also the unique struggles faced by young female protagonists living in two different cultural and political envir
10.18052/www.scipress.com/ILSHS.66.10
Keywords: (thesoz)Kinderliteratur; (thesoz)Konflikt; (thesoz)Trauma; (thesoz)Krieg; (thesoz)Flucht; (thesoz)Einwanderung; (thesoz)Waise; (thesoz)Postkolonialismus